Efek Anti Inflamasi Ekstrak Daun Salam (Syzygium Polyanthum) - Widiyanto, Bagas; Sampurna, Sampurna; Rizki Dewinda Putri, Cantika; Adiba Aysar, Nisrina; Brave Sinatrya, Muhamad (Green Publisher Indonesia, 2025)
Inflammation or inflammation is characterized by increased levels of pro-inflammatory mediators such as IL6, IL1, TNF- and CRP proteins in the blood. One of the mechanisms is through the activation of TLR-4 and NF-κB. Natural remedies have developed, one of which is using bay leaves (Syzygium polyanthum). Bay leaves contain flavonoids, tannins, and saponins that have the potential to be anti-inflammatory. This study aimed to determine the effect of bay leaf extract on IL-6, IL-1, TNF- and CRP protein levels in male white rats of wistar strain induced by 1% carrageenan. Methods: An experimental type of research with a